Syntactical Errors Made by the Teachers of Indonesian Vocational School ‘SMK Wahidin’ Cirebon in Writing Scientific Abstracts - Ervina CM Simatupang; Susiyanti Rusyan; Puspita Sari; Deden Novan Setiawan Nugraha (Universitas Cokroaminoto Palopo, 2022)
Based on the regulation the Ministry of State Apparatus Empowerment and the Bureaucratic Reform of the Republic of Indonesia Number 16 Year 2009 regarding Position of Teacher Functional Score and Credit Figures, teachers are required to write scientific papers as one of the requirements to apply for a functional promotion. However, this rule seems to be difficult for the teachers to be done since writing scientific papers is a big professional challenge for most school teachers. At SMK Wahidin Cirebon, West Java, Indonesia, for example, a vocational school in Cirebon, West Java, Indonesia, there was found that the teachers are still clueless and negligent in writing the article. Therefore, that situation triggered the research team (the writers) to give the workshop on how to write the scientific papers, especially writing the abstract. Furthermore, to evaluate the teachers’ writing ability, this paper was written to investigate the syntactical errors made by the teachers of Indonesian Vocational School ‘SMK Wahidin’ in writing abstract for a scientific paper. It involved 8 abstracts which were written by the teachers at SMK Wahidin. The data were collected by observation and documentation, and then analyzed using Syntactic theory proposed by Radford (2004) that was developed from the Chomsky’s theory. The research results show that the dominant syntactical errors made by the teachers are syntactical errors in using the verbs. Meanwhile, the factors that influenced the teachers’ syntactical errors are mother tongue interference and unawareness of the grammatical rules.